2019
DOI: 10.30722/ijisme.27.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality in Higher Education

Abstract: Virtual reality (VR) is an interactive experience which immerses the user in a digital environment through a sense of presence. In the context of providing an active learning experience, virtual reality has the potential to improve learning outcomes for biomedical science students as it allows the visualisation of and interaction with digital representations of dynamic objects and complex concepts. Studies in bioscience and medical education have shown mixed results pertaining to the benefits of VR as a learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 31 publications
(68 reference statements)
1
15
0
1
Order By: Relevance
“…Regarding the cognitive effects of the immersive virtual reality environments obtained from the meta-thematic analysis, it was seen that codes such as providing permanent learning, increasing the comprehension of the lesson, increasing the focus on the lesson, providing active participation, providing in-depth learning, self-regulated learning, and allowing the student to learn according to his/her level were created. This finding is in line with the findings of other research (Hwang & Hu, 2013;Liou et al, 2017;Fabris et al, 2019;Tepe, 2019;Akman & Çakır, 2020;Chien, Hwang & Jong, 2020;Kalkan, 2020;Tai et al, 2020). In the study of Sakdavong, Burgues, and Huet (2019) on self-regulation in virtual reality environments, it was found that immersive environments and interaction with the environment were very effective on self-regulated learning.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Regarding the cognitive effects of the immersive virtual reality environments obtained from the meta-thematic analysis, it was seen that codes such as providing permanent learning, increasing the comprehension of the lesson, increasing the focus on the lesson, providing active participation, providing in-depth learning, self-regulated learning, and allowing the student to learn according to his/her level were created. This finding is in line with the findings of other research (Hwang & Hu, 2013;Liou et al, 2017;Fabris et al, 2019;Tepe, 2019;Akman & Çakır, 2020;Chien, Hwang & Jong, 2020;Kalkan, 2020;Tai et al, 2020). In the study of Sakdavong, Burgues, and Huet (2019) on self-regulation in virtual reality environments, it was found that immersive environments and interaction with the environment were very effective on self-regulated learning.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…In addition, their freedom in the virtual environment was diametrically opposed to the strict protocols in the traditional laboratories, this was pointed out by the participants. The positive evaluation of the learning tool is important because if it offers an authentic and engaging learning experience then students are led to greater engagement, pleasure and interest in the learning object (Fabris et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, Virtual Reality has returned to the foreground, as well as the interest for its educational use, a fact that is reflected in the rapid increase of relevant research (Nesenbergs, Abolinis, Ormanis & Mednis, 2021;Fabris, Rathner, Fong & Sevigny, 2019;Menin, Torchlsen & Nedel, 2018). Virtual Reality (VR) is defined as the creation of an artificial interactive environment or Virtual Environment that human perceives as real.…”
Section: Introductionmentioning
confidence: 99%
“…Experts' opinions and suggestions are carefully adopted during the entire interview, providing a profound, diverse, and valuable viewpoint for the following teaching experiment. Specifically, the interview involves basic information, such as educational background, job title, professional level, the application of modern teaching methods in venues and equipment during physical education, and the attitudes toward modern teaching methods [ 26 , 27 ]. Table 1 provides the basic information of experts obtained through the interview.…”
Section: Optimization Of the Teaching Mode Of Preschool Physical Educ...mentioning
confidence: 99%